Myanmar Economic Monitor, October 2015 : Staying the Course on Economic Reforms - World Bank Group (World Bank, Washington, DC, 2015)
The Myanmar Economic Monitor (MEM) aims to periodically take stock of economic development and highlight economic prospects and policy priorities in Myanmar. Myanmar grew at an estimated 8.5 percent in real terms in 2014/15. The MEM touches on continued recovery in growth, public consumption, private investment, services, investment in manufacturing and industry, rebound in agriculture and the impact of floods. The monitor examines foreign trade and investment; the inflation, monetary and exchange rates; fiscal policy; and Myanmar’s economic outlook. The Policy Watch section covers a few selected priority issues closely related to Myanmar’s overall economic developments and outlook.